REDUCTION ABILITY OF CURCUMIN AND DERIVATIVES ON FERRI : A MOLECULAR DYNAMIC STUDY - Ari Sudarmanto, Bambang Sulistyo; Margono, Supardjan Amir (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2002)
Molecular dynamics (MD) simulation has been applied to curcumin, 4-methyl curcumin and 4-isopropil curcumin. They have reducting activities on Ferri to Ferro. A computation method used is AM1 (Austin Model 1) semiempiric method. Studying of computation is arranged to theoretical studying of structure and reactivity relationship on these molecules without solvent interaction (in vacuo). The time of simulation is taken from 0 â 10 ps (pico secon) with interval 0,0005 ps on 300oK. The result of experiment that has been proposed from the MD simulation is the structure of conformation trajectory of each molecules. By considering total energy and potential energy changes to time of simulation, along with the change of bonding length, bonding angle, and the atomic charges of ï¢-diketon active site to time of simulation. Reactivity of these molecules are analyzed from the geometric shape of the active site indicated that 4-isopropyl curcumin was the most reactive than the other to produce complex with Ferri, while 4-methyl curcumin within the complex was easiest in the reduction of Ferri to Ferro.Key words : molecular dynamic, curcumin, reduction